KADAR PROTEIN SERAT KASAR LEMAK TEKSTUR MARNING JAGUNG LOKAL DESA SILLU KABUPATEN KUPANG DENGAN INTERAKSI FAKTOR KONSENTRASI Ca (OH)2 DAN LAMA PERENDAMAN BIJI JAGUNG KERING - Abidin, Zainal; Harini, Titik Sri (JURNAL AGRISA, 2023)
The aim of the research was to determine the levels of protein, fiber, fat and corn marning texture given the interaction of lime concentration and soaking time. The problems with processed dried shelled corn products such as marning, emping, corn tortilla chips are that the texture is not crispy, less fluffy, relative nutritional components do not comply with SNI, the taste of the product is less varied and consumers don't like it so marketing is limited. The hard and less fluffy texture of corn kernels is caused by the complex network of starch and starch-protein complexes forming a hard matrix, so the right solution is needed. Several studies were carried out but the results were not optimal because the lime concentration, boiling time and soaking time were not correct, so research was needed to loosen the chemical bonds between starch complex compounds and hard starch-protein complexes by entering high-temperature lime water, which would result in cross-linking with ions. Calcium ions (Ca2+), the network is more open and tense which cannot be reversed during drying and frying so that the complex compound matrix network expands, giving crispiness to the product. This research is a factorial study of 2 factors: lime concentration and soaking time with 6 treatment interactions: A1B1, A1B2, A1B3, A2B1, A2B2, A2B3. The replication was 3 times so there were 18 experimental units. The research results show that lime concentration and boiling time influence the chemical and physical properties and marning of corn. Local corn marning meets the Quality Standards for Marning Corn according to SNI 01-4300-1996 in terms of texture and chemical properties of corn marning. The best treatment A1B3 for protein content is 8.729%; the best treatment A1B1 for fat content is 13,814%; The best treatment A1B3 for fiber content is 12.998%. The best treatment A1B1 for the physical properties of local corn marning with a texture value of 1580,500 mm/g.sec.